Menurunkan Perilaku Agresif Siswa Taman Kanak-kanak Melalui Aktivitas Bermain Peran Prososial - Desvianti, Erika (Generasi Emas, 2023)
One of the problems that parents and teachers often complain about is aggressive behavior in kindergarten students because this aggressive behavior is a problem that often occurs in children and is always there in every school year. Several studies have shown that since childhood the handling and prevention of aggressive behavior must be done. This is done in order to prevent disruptive behavior that may arise in the future and have long-term effects so that it can cause negative effects on children and continue until they are adults. One effort that can be done to reduce aggressive behavior is to develop prosocial behavior. Aggressive individuals are taught to behave in non-aggressive ways. This approach is felt to be more effective in reducing aggression by using the principle of behavior modification learning that focuses on strengthening non-aggressive behavior. Prosocial behavior developed using role playing methods with prosocial themes. The development of this prosocial behavior involved 12 kindergarten students in Yogyakarta. Prosocial behavior is taught using several indicators of prosocial behavior such as helping, sharing, entertaining and collaborating. The Time-series Group Nonequivalent No-Treatment Control Group quasi-experimental design is the design used in this study. Based on the results of this research data analysis it is proven that the aggressive behavior of students in Kinder garten can be reduced through prosocial role playing significantly in the experimental group when compared to the aggressive behavior group in the control group (z=-2.169; p<0.05).